ZigBee environment for indoor localization - Chieh K.S.; Keong N.Y.; Burhan M.F.; Balasubramaniam N.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Nearest neighbor search; Pattern recognition; Zigbee; Indoor environment; Indoor localization; Indoor localization systems; Indoor locations; K nearest neighbor algorithm; Prediction accuracy; Indoor positioning systems